Improvement of several indicators of physical and biological properties of soil after adding crops biomass residues and yield of upland rice - Barus, Junita; Lumbanraja, Jamalam; Sudarsono, Hamim; Dermiyati, D (Journal of Degraded and Mining Lands Management, 2019)
Returning and addition of organic material to soil is a key to protecting the soil, plants, and the environment. A study aimed to elucidate the effect of residual biomass application on some indicators of soil physical properties, abundance of earthworms and soil microbial activities was conducted in Kebun Percobaan (KP) Natar, BPTP Lampung from February to July 2017. The treatments were three types of crops biomass residues, i.e., maize stover, rice straw, and soybean stover (fresh or compost). The dosage rates were 0, 2.5, 5.0, 7.5, and 10 t/ha. The treatments were arranged in a randomized block design with three replicates. Upland rice (Inpago 9 variety) was planted after two weeks application of biomass residues treatments. The results showed that application of crops biomass residues improved bulkdensity and significantly increased soil water content at the high dose of biomass residues (7.5 or 10 t/ha). The amount and weight of earthworms with added of compost biomass was significantly correlated with soil water content (r values 0.491 and 0.376, respectively). The dose of biomass residues had a significant effect on soil respiration that the highest soil respiration was obtained in maize compost biomass treatment (at 12 weeks observation) was 31.7 and rice straw compost (at 8 weeks observation) which was 30.19 mg/hour/m2 C-CO2.